CONSUMER WELL-BEING: PERAN BRAND AUTHENTICITY DAN DAMPAKNYA TERHADAP CONSUMER CITIZENSHIP BEHAVIOR - Gunawan, Nanang; Suharyono, Suharyono; Sunarti, Sunarti (FIA UB, 2021)
This article aims to deepen knowledge about the importance of the concept of consumer well-being Â in marketing research, as well as to build propositions related to the potential for consumer well-being and its consequences for marketing outcomes. Through an in-depth study of the existing literature, it can be revealed that CWB is an important construct in marketing research and consumer behavior. CWB measurement can be done by measuring consumer satisfaction which contributes to several positive states of consumers in the form of positive emotions, attachments, relationships, meaning, and achievement (PERMA). In addition, this article succeeded in building a proposition that brand authenticity can have a significant effect on CWB and marketing outcomes in the form of consumer citizenship behavior. The relationship between these variables is based on self-determination theory.